The Development of a Program to Enhance the Ethical Leadership Qualities of Teachers under the Supervision of the Secondary Educational Service Area Office Khon Kaen - Namwongsa, Rachai; Noirit, Surachat (Interdisciplinary Academic and Research Journal, 2023)
Ethical leadership is important because it enables the person in leadership to make decisions and guide actions based on sound ethical values, acting with professional ethics. They are the person who always does what is right, is honest, can be trusted, is respectable and good. Being an example of an ethical leader thus promoting ethical practices in the organization seriously makes them respect and trust in management. Thus, the aims of this research were as follows: 1) to study the current qualities, the desired qualities, and the requirements for enhancing the ethical leadership qualities of teachers under the supervision of the Secondary Educational Service Area Office Khon Kaen, and 2) to develop a program to enhance the ethical leadership qualities of teachers under the supervision of the Secondary Educational Service Area Office Khon Kaen by employing research and developmental methods. The study was conducted in two phases: Phase 1 involved studying the current qualities, the desired qualities, and the requirements for enhancing the ethical leadership qualities of teachers under the Secondary Educational Service Area Office Khon Kaen. The sample group, which was selected by stratified random sampling, consisted of 346 teachers and administrators under the supervision of the Secondary Educational Service Area Office Khon Kaen. The research tool, which was utilized, was a rating scale questionnaire. In Phase 2, a program was developed to enhance the ethical leadership qualities of teachers under the supervision of the Secondary Educational Service Area Office Khon Kaen, based on the best practices of six model schoolteachers and administrators. The program was created and evaluated by five qualified individuals, who had been purposively selected. The research methodology employed an assessment tool to evaluate the suitability and feasibility of the ethical leadership development program for teachers. The statistical analysis of the data consisted of frequencies, percentages, means, standard deviations, and the necessary index. The research findings indicated the following: (1) Overall, the current state of the ethical leadership qualities of teachers was high. The most desirable state of the ethical leadership qualities of teachers was at the highest level. The requirements of the ethical leadership qualities of teachers were ranked in descending order as follows: being effectiveness-oriented, being respectful, being public-minded, being fair, being responsible, and being honest. (2) The ethical leadership development program for teachers, under the supervision of the Secondary Educational Service Area Office Khon Kaen, was comprised of 1) principles and importance, 2) objectives, 3) content, 4) developmental methods, and 5) evaluation & assessment. The program comprised six Module-s: Module-1: Fairness, Module-2: Honesty, Module-3: Responsibility, Module-4: Public-mindedness, Module-5: Effectiveness-orientation, and Module-6: Respect. Overall, the results of the program evaluation indicated high suitability and the highest feasibility.